Model for B1 Imaging in MRI Using the Rotating RF Field. (19th May 2014) - Trakic, Adnan; Jin, Jin; Weber, Ewald; Crozier, Stuart
Abstract : Conventionally, magnetic resonance imaging (MRI) is performed by pulsing gradient coils, which invariably leads to strong acoustic noise, patient safety concerns due to induced currents, and costly power/space requirements. This modeling study investigates a new silent, gradient coil-free MR imaging method, in which a radiofrequency (RF) coil and its nonuniform field (B 1 + ) are mechanically rotated about the patient. The advantage of the rotating B 1 + field is that, for the first time, it provides a large number of degrees of freedom to aid a successful B 1 + image encoding process. The mathematical modeling was performed using flip angle modulation as part of a finite-difference-based Bloch equation solver. Preliminary results suggest that representative MR images with intensity deviations of <5% from the original image can be obtained using rotating RF field approach. This method may open up new avenues towards anatomical and functional imaging in medicine.